PENERAPAN METODE LATIHAN UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR MURID TAMAN KANAK-KANAK KARNIDA BAHAGIA PERUM SIDOMULYO KOTA PEKANBARU - Julianidar Julianidar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
Study of development of physical motorik in Kindergaten must be done with the technique and way of interesting, so that child motivated to follow the study activity. As characteristic of study system in Kindergaten that is learn at the same time play at and play at at the same time learn. Play at to represent the basic requirement every child. Its meaning, playing at to represent one of most phenomenon of natural or natural in phase of child life. Effort teacher to develop the motoric child not yet showed the maximal result and lack of physic appliance supporting study, so that child of indigent of application of teacher boldness, require to be by effort of study development which inspirative, inovative, challenging, pleasing and motivating and can give the positive response learn to child to increase process and development of motoric child. This research aim to description of applying of practice technique to increase skill of motoric of child and description of applying of practice technique to increase activities of learn child in TK Karnida Bahagia of Perum Sidomulyo Pekanbaru. Data collecting of research at even semester of study year 2009-2010, The research instrument that is sheet of observation of activity of child and teacher. Analyse the data by qualitative usher the cycle, while analysis of result of domination motoric with the quantitative approach. The research result got by conclusion that applying of practice technique can uplift skill the motorik of child and applying of practice technique can improve the activity learn child in TK Karnida Bahagia of Perum Sidomulyo Pekanbaru. Applying of practice Technique can give the positive respon, capable to improve the effectiveness of domination of motorik child. And to reaching of study result by playing at optimal, have to be supported ably the understanding of teacher to structure of anatomy of body and function. With this understanding is teacher can create the creative game, inspiration, innovate, challenging, pleasing, and motivating, supporting growth of ability motoric needed by child.Keywords: practice technique, motoric